Molecular dynamics approach to thin‐film liquid phase change phenomena on functionally gradient wettability surface. (17th June 2020) - Thakur, Md Shajedul Hoque; Islam, Mahmudul; Alam, Shahriar; Hasan, Mohammad Nasim; Mitsutake, Yuichi; Monde, Masanori
Abstract : An atomistic model of functionally gradient wettability (FGW) surface for molecular dynamics (MD) simulation has been proposed and developed. Using the present model, a non‐equilibrium MD study has been conducted to investigate the effects of FGW on liquid thin film phase change characteristics over the FGW surface. A power function has been considered as the wettability governing function of the FGW surface and by varying its function parameter, various FGW surfaces have been studied. The simulation results show that the function parameter can be a significant modulation parameter for heat transfer characteristics associated with the phase transition. To gain insight into any additional heat transfer mode associated with the FGW surface, the wall heat fluxes have been compared with linear mixture rule predictions. It is found that, along with conduction heat transfer through the interface between solid FGW surface and liquid thin film, there exists convective heat transfer along the wettability gradient direction. This additional heat transfer mode, which is not present for uniformly wetted surfaces, causes significant enhancement of phase change characteristics. The results of the present MD simulation have been found consistent with macroscopic prediction based on classical thermodynamics theory.